Dentists' attitudes towards chairside medical conditions screening in a dental setting in Saudi Arabia: an exploratory cross-sectional Study - Saba Kassim; Badr Othman; Sakher AlQahtani; Alemad Mustafa Kawthar; Sterling M. McPherson; Barbara L. Greenberg (BMC, 2019)
Abstract Background Screening for medical conditions (MCs) of public health importance is a first step in disease prevention and control. Prior studies in the United States found oral health care providers (OHCPS) embrace screening for increased risk of medical conditions in the dental setting. Our objectives were to assess Saudi Arabian (SA) dentist's attitudes, willingness and perceived barriers towards implementing screening for MCs into their dental practices. Methods A self-administered, 5-point Likert Scale (1 = very important/willing to 5 = very unimportant/unwilling) questionnaire was given to a convenience sample of 190 practicing dentists. Friedman nonparametric analysis of variance was used to compare responses within each question. Results Of the 143 responding dentists the mean age was 31 years; 102 (71%) were men. The majority felt it was important for a dentist to screen for cardiovascular disease (98.6%), hypertension (97.9%), diabetes (97.9%), human immunodeficiency virus (HIV) (97.9%), and hepatitis C virus (98.6%). Respondents were willing to refer a patient to a physician (97.9%); send samples to an outside laboratory (96.1%); conduct screening that yields immediate results (96.2%); and discuss results immediately with the patient (93.7%). Respondents were willing to measure/collect blood pressure (67.2%); weight and height (63.7%); and finger stick blood (54.6%). The whole responding dentists (100%) reported time as an important barrier. Respondents were significantly more willing to refer a patient for consultation than send samples to an outside laboratory (mean ranks: 2.32, 2.81, P < 0.001); significantly more willing to measure blood pressure than take oral fluids for salivary diagnostics (mean ranks 2.22, 2.75, p = 0.003). Insurance was significantly (P < 0.05) less important barrier than time, cost, patients' willingness or liability (mean ranks 3.56, 2.63, 3.00, 2.79, 3.02, respectively). Conclusions The majority of dentists in this study reported positive attitudes towards and willingness to perform medical screenings in their practice. Time was an important factor.